Construction of the Discrete Hull for the Combinatorics of a Regular Pentagonal Tiling of the Plane - Ramirez-Solano, Maria (MATHEMATICA SCANDINAVICA, 2016)
The article A "regular" pentagonal tiling of the plane by P. L. Bowers and K. Stephenson, Conform. Geom. Dyn. 1, 58-86, 1997, defines a conformal pentagonal tiling. This is a tiling of the plane with remarkable combinatorial and geometric properties. However, it doesn’t have finite local complexity in any usual sense, and therefore we cannot study it with the usual tiling theory. The appeal of the tiling is that all the tiles are conformally regular pentagons. But conformal maps are not allowable under finite local complexity. On the other hand, the tiling can be described completely by its combinatorial data, which rather automatically has finite local complexity. In this paper we give a construction of the discrete hull just from the combinatorial data. The main result of this paper is that the discrete hull is a Cantor space.